Pengembangan Panel Surya 120 Wp Dengan Solar Tracker Double Axis Sebagai Bahan Pembelajaran Mahasiswa di Program Studi Teknik Mesin UHN - Siagian, Parulian (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2022)
The current need for electrical energy sourced from fuel oil is increasingly running out and expensive. Anticipating future energy crises will require creativity from energy observers in finding alternative energy sources that can improve people's welfare. We get solar energy for free throughout the year with good intensity, one of which is because Indonesia's position is on the equator. To convert solar heat from the outside into electrical energy, several converter technologies such as solar panels are needed. Solar panels that are directly exposed to solar radiation can produce efficient electrical energy depending on the position of the incident light that hits the surface of the solar panel. Solar panels that can follow the direction of the radiation source at an angle of 90o to the surface of the solar panel must require a solar tracker. Solar tracker is a control circuit that is able to detect and follow the direction of the sun so that the solar panel is always perpendicular to the sun so that the light intensity received by the panel is optimal by adjusting the motor movement. The results of this study indicate a light intensity of 408.10 W/m2 at a wind speed of 1.08 m/s produces a current of 19.20 Volts with an efficiency level of 4.21% at the incoming energy (Pin) 279.05 and the outgoing energy ( Pout) 11.77 W.